Psychological Impact of Dengue Fever in Nepal: A Qualitative Study - Adhikari, Preeti; Paudel, Sushila (International Journal of Atharva, 2026)
Background: This study explored the emotional experiences, coping responses, and cultural influences among individuals affected by dengue fever in the Kathmandu Valley.Methods: A qualitative descriptive design was used. Ten adults (≥18 years) who had experienced dengue within the past two to three years and lived in the Kathmandu Valley (Kathmandu, Lalitpur, Bhaktapur) were recruited through purposive and snowball sampling. Semi-structured interviews were conducted, and a nurse and a psychologist were included as key informants to triangulate patient perspectives. Data were analyzed using Braun and Clarke’s thematic analysis.Results: Participants experienced strong psychological distress including fear of death, panic, helplessness, and emotional numbness. Some reported anxiety, irritability, and reduced concentration even after recovery. Coping strategies were largely passive such as rest, sleep, minimal emotional expression, and strong reliance on family support. Community responses were generally supportive.Conclusion: Dengue fever carries a meaningful psychological burden that extends beyond physical recovery. Strengthening mental health support, integrating basic psychological first aid, and improving community awareness could enhance holistic dengue care and promote emotional well-being among affected individuals in Nepal.